The Effect of Animation on The Society During The COVID-19 Pandemic - Bahaa Mustafa (مجلة العصر للعلوم الانسانية والاجتماع, 2023)
Animation has always occupied a special space in the hearts and minds of those that have consumed the media by making it possible to bring to life what would otherwise be impossible. It is because of the spectacle of seeing what otherwise wouldn’t be possible that makes animation so magical, and the almost magical effects that can be achieved through animation has captivated the minds of many throughout history and its many different forms. Animation’s development went hand in hand with the development of the movie or motion picture which captured real-life, and this interdependence is displayed through the development of shared technology that both mediums utilize. The industry’s contributions towards the art of telling complex stories and narratives through gestures and different perspectives from its early days until now, This research project delves into the importance of animation and its cross-medium contributions to many of the things that are now taken for granted. This research project delves into the importance of animation This paper attempts to understand the links between culture and animation, how animation has taken place during (covid-19), how animation have been studied , Animation and how it affected society during (covid-19) and Animations industry growth during (covid-19).